Recent Advances in Mathematical Aspect in Engineering - Ellahi, Rehmat; Sait, Sadiq M.; Xu, Huijin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The present text is an edited Special Issue in reprint form. This Special Issue took the opportunity to invite researchers to contribute their latest original research findings, which were either advances in the state-of-the-art of mathematical methods, theoretical studies, or experimental studies that extend the bounds of existing methodologies to new contributions, addressing current challenges and engineering problems on "Recent Advances in Mathematical Aspect in Engineering". Although this reprint is not a formal textbook, it will definitely be useful for university teachers, research students and industrial researchers, and will assist in overcoming difficulties while dealing with the nonlinear governing equations of fluid mechanics, energy, heat transfer, steady and unsteady flow problems, nanofluids, thermodynamics, magnetohydrodynamics, peristaltic and blood flow. For nonlinear and coupled differential equations, it is often more difficult to achieve an analytic solution or even a numerical one. This reprint has successfully handled this challenging task with the techniques reported within. In addition, the findings of the simulations are logically realistic and meet the standard of sufficient scientific value.